2021
DOI: 10.3390/v13071355
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Surveillance for Risk Assessment in the Context of a Phase 2 Clinical Trial of Type 2 Novel Oral Polio Vaccine in Panama

Abstract: Environmental surveillance was recommended for risk mitigation in a novel oral polio vaccine-2 (nOPV2) clinical trial (M5-ABMG) to monitor excretion, potential circulation, and loss of attenuation of the two nOPV2 candidates. The nOPV2 candidates were developed to address the risk of poliovirus (PV) type 2 circulating vaccine-derived poliovirus (cVDPV) as part of the global eradication strategy. Between November 2018 and January 2020, an environmental surveillance study for the clinical trial was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There are several indications that this was due to low-level sample contamination during processing of stool samples, leading to aberrant laboratory results due to the high sensitivity of the RT-PCR assays. These include the first nOPV2-positive samples being obtained within 8 days of the first vaccination with low-dose nOPV2-c1), there being no geographic relationship between vaccine use and baseline positive infants, and environmental surveillance of the study area did not find any type 2 positive samples [ 20 ]. Furthermore, most positive samples were nOPV2-c1 despite the simultaneous use of nOPV2-c2.…”
Section: Discussionmentioning
confidence: 99%
“…There are several indications that this was due to low-level sample contamination during processing of stool samples, leading to aberrant laboratory results due to the high sensitivity of the RT-PCR assays. These include the first nOPV2-positive samples being obtained within 8 days of the first vaccination with low-dose nOPV2-c1), there being no geographic relationship between vaccine use and baseline positive infants, and environmental surveillance of the study area did not find any type 2 positive samples [ 20 ]. Furthermore, most positive samples were nOPV2-c1 despite the simultaneous use of nOPV2-c2.…”
Section: Discussionmentioning
confidence: 99%
“…Shedding analysis showed that nOPV2 was more genetically stable and had a lower risk of reverting to virulence – the cause of outbreaks of cVDPV – compared with mOPV2 ( 13 ). Also, nOPV2 could not be detected in wastewater in the neighborhoods close to the trial sites ( 14 ). WHO authorized the use of nOPV2 to control outbreaks of cVDPV2 through its Emergency Use Listing (EUL) procedure in November 2020 after the phase 2 studies were completed.…”
mentioning
confidence: 99%